Artemis Fowl : The Eternity code - Colfer, Eoin (Colfer, Eoin. Artemis Fowl, 2003)
Artemis Fowl creates an extraordinarily powerful computer with stolen fairy technology, but his business deal hopes go sour when a Chicago businessman steals his invention and mortally wounds Artemis's loyal bodyguard.